2021
DOI: 10.1111/ped.14543
|View full text |Cite
|
Sign up to set email alerts
|

Trace element levels in mature breast milk of recently lactating Japanese women

Abstract: Background Many trace elements are essential for infant growth and development during early life. Their concentrations in breast milk vary depending on social and economic factors. Nonetheless, the present available values in Japan were derived from lactating mothers approximately 15 years ago. Methods Healthy mothers who gave birth to a single infant after 37 weeks of gestation at Teikyo University Hospital were recruited between July 2016 and December 2017. They were encouraged to collect breast milk samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
(100 reference statements)
1
15
0
Order By: Relevance
“…The variations in the trace elements levels might be due to several factors such as lactation stages, geographical regions, dietary intakes or trace element supplements that were taken by some of the participants. Consistent with the previous reports, positive signi cant correlations also were observed for most of the elements (r > 0.40, p < 0.001) except for Cu-Mn (Li et al, 2016;Motoyama et al, 2021). The limitation of this study includes the small size population due to challenges in recruiting participants.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The variations in the trace elements levels might be due to several factors such as lactation stages, geographical regions, dietary intakes or trace element supplements that were taken by some of the participants. Consistent with the previous reports, positive signi cant correlations also were observed for most of the elements (r > 0.40, p < 0.001) except for Cu-Mn (Li et al, 2016;Motoyama et al, 2021). The limitation of this study includes the small size population due to challenges in recruiting participants.…”
Section: Discussionsupporting
confidence: 81%
“…Although, no optimal levels of Cu in human milk were established yet in human milk.The median Se concentrations found in this study were 23.6 µg/L in the rst month and then decreased to 14.15 µg/L at 3 months and 10.41 µg/L at 6 months postpartum. Another study also found similar level of Se at 1-month which was 22(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) µg/L but higher level at 3 months postpartum, of 21 (16-25) µg/L (Motoyama et al, 2021). However, a previous study by Mandiá et al (2021) reported lower mean Se values of 8.87 µg/L in the mature milk compared to the current study which was 24.82 µg/L.…”
mentioning
confidence: 74%
“…In total, 9992 unique abstracts were identified, 1001 full texts were assessed, and 139 articles met inclusion criteria, of which 28 articles reported HM micronutrients [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] ] ( Figure 1 ). The main reasons for excluding articles were: no HM analytes of interest were reported ( n = 89); no infant anthropometrics or only birth anthropometrics were reported ( n = 512); or no associations between HM analytes and infant anthropometrics were reported ( n = 165).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 28 included micronutrient articles ( Table 1 and Supplementary Table 3 ), 8 (29%) were published before 1998 [ 27 , 29 , 31 , 35 , 38 , 39 , 41 , 45 ]; 19 (67%) were published in 2010 or later [ 25 , 26 , 28 , 30 , [32] , [33] , [34] , 36 , 37 , 40 , [42] , [43] , [44] , [46] , [47] , [48] , [49] , [50] , [51] ]. These 28 articles represented 26 unique studies involving 2526 dyads; 17 studies were conducted in low- or middle-income countries (according to World Bank criteria) [ [24] , [25] , [26] , 30 , [32] , [33] , [34] , [36] , [37] , [38] , [39] , [41] , [42] , [43] , [44] , 46 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Determination of Serum Se Concentrations Serum Se concentrations were measured by inductively coupled plasma mass spectrometry (ICP-MS; iCAP Q, Thermo Fisher, Waltham, MA). 28 Blood samples collected before the initiation of first dialysis session were used to determine serum Se levels. Serum Se levels and iron parameters were determined in the same samples or samples obtained within 1 month.…”
Section: Patientsmentioning
confidence: 99%